UNUSUAL DERMATOLOGICAL MANIFESTATION OF GRAVES’ DISEASE IN AFRO-CARIBBEAN PATIENTS - George, Colefle (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES To describe an unusual skin manifestation of Graves’ disease in Afro-Caribbean patients. METHODOLOGY Seven patients referred to a private endocrine clinic for management of hyperthyroidism between 2000 and 2021 are described. They all had laboratory confirmation of a thyrotoxic state by demonstration of suppressed TSH and elevated Free T4. Graves’ disease was identified as the aetiology by the presence of at least one of the following: exophthalmos, diffuse goitre with bruit, elevated TSH- receptor antibodies or diffuse uptake on a technetium scan. At the time of consultation, the patients were noted to have unusual skin lesions, which were photographed either with their consent (six adult patients) or with the consent of the parent (one child). RESULTS The patients ranged in age from 9 to 52 years at the time of presentation. They were of Afro-Caribbean origin. They were all markedly thyrotoxic. They were noted to have skin lesions in areas other than the typical pre-tibial area. The lesions were non-pruritic and non-erythematous and were not in keeping with urticaria. The appearance in each of the patients was similar and was either papular or nodular. Areas involved included the chest, back, forearm, hand and foot, thigh and face. One patient (the first one identified) had biopsy that showed a perivascular lymphocytic infiltrate in the mid-dermis. CONCLUSION Nodular dermopathy in areas other than the pre-tibial region should be recognized as a dermatological manifestation of Graves’ disease in Afro-Caribbean patients.